Dinamika Pemerintahan Desa di Kawasan Pesisir - Satia Ningsih; Eka Suaib; Bakri Yusuf (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2022)
This study discusses the dynamics of village government in building self-reliance in coastal areas. The research method used is descriptive qualitative. Data collection techniques through observation, interviews, and documentation. The findings of this study indicate that the dynamics of village governance in general have led to independence in terms of governance, development implementation and community empowerment.